Effect of activated carbon/graphite on enhancing anaerobic digestion of waste activated sludge - Wu, Fei; Xie, Jiaqian; Xin, Xiaodong; He, Junguo (Frontiers in Microbiology, 2022)
The conductive media was capable to enhance anaerobic digestion and promote direct interspecific electron transfer (DIET). In this study, the effect of activated carbon- and graphite-conductive media with their particle size changes on promoting anaerobic digestion efficiency of waste activated sludge were experimentally studied. The results showed that the promotion effect of anaerobic digestion arrived to an optimal level when the particle size of activated carbon and graphite was 100 mesh and 400 mesh respectively, while the cumulative biogas production increased to 13.8% and 12.5% respectively as compared with the blank group. The degradation rates of VSS, TCOD, total protein and total polysaccharide were improved with the decrease (to the optimal particle size) of particle size of such two carbon-conductive media. Activated carbon was capable to promote the hydrolytic acidification stage in anaerobic digestion of waste sludge. When the particle size reduced to the optimal particle size, the promoting effect could be strengthened for producing more hydrolytic acidification products for methanogenesis. However, the graphite group presented no significance for the enhancement of hydrolytic acidification, but it was capable to promote the consumption of hydrolytic acidification products. Moreover, the promoting effect could be strengthened with the particle size reduced to the optimal particle size so as to improve the methanogenesis process and the whole anaerobic digestion efficiency of waste sludge.